Diet Composition and Dietary Diversity in the Cambodian Mekong Delta: Evidence from a Rural Household Survey - Phay, Sokcheng (WorldFish, 2024)
This study is based off a rural household survey conducted in mid-2023 in Cambodia’s Lower Mekong Delta. The purpose of the survey was to explore current dietary practices and food security under the CGIAR Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience (AMD). Households spend an average of 9,000 KHR (2.25 USD) daily per adult on food, with IDPoor households spending less (8,000 KHR or 2 USD). Food expenditures account for 46% of household budgets, rising to 48% for IDPoor and female-headed households. Daily diets consist primarily of rice (34%), vegetables (22%), and fruits (11%), with 78% of food purchased and the rest from home production. While three-quarters of surveyed individuals achieve medium to high dietary diversity, diets are high in carbohydrates and sugars, raising concerns about nutritional quality. Food insecurity affects 50% of households, with IDPoor and female-headed households disproportionately impacted. Interventions should promote healthier diets through aquatic foods, home gardens, and awareness campaigns, while policies should prioritize vulnerable groups to improve nutrition, food security, and livelihoods.